Rethinking news values and newsroom practices in postcolonial contexts and the construction of subaltern identities - Mugari, Zvenyika Eckson (University of Witwatersrand, 2017)
This study blends critical discourse analysis with ethnographic inquiry into the nature of discursive constructions of subaltern identities in postcolonial contexts of news production by mainstream news organisations in colonial and post-independence Zimbabwe. The main thrust of the study was to establish continuities and disjunctures in newsroom cultures of production in colonial and in post-independence situations in which marginalized former colonial subject populations are caught up. It employs a multidimensional synchronic and diachronic case study approach where one newspaper organization specifically The Herald’s coverage of episodic forced removals of subject populations is studied across different historical moments. The paper’s coverage is then critically compared and contrasted with that of other newspapers then in existence and contemporaneously operating at that time. The selected historical moments of forced removals were only heuristically chosen to the extent that they demonstrated the greatest potential for drawing media attention and thus present an opportunity for the ordinary subaltern populations to appear in the news. The content analysis generally tended to demonstrate that the same canibalesque evident in the newsification of subjects of colonial domination was pretty much evident in the way news in the post-independence period constructed the subalternity of marginalized groups. The institutionalization of the so called universal news values tend towards symbolic annihilation of subaltern ways of knowing. The newspaper as a cultural form, this study established, remains ill-suited and instrumentalised to serve the ends of emancipation and empowerment. The press in Zimbabwe retain many traces of its colonial parentage with serious negative ramifications for their claim to a democratic function